Self-acceptance in today’s young people - Călin, Mariana Floricica; Tasențe, Tănase (Technium Social Sciences Journal, 2022)
Acceptance of the self, others and the environment is a force for personal change that has its origins in many eastern and western cultures. The benefits of accepting are described by many cultures through religious literatures (New Testament, Tao Te Ching, Buddhist Scriptures, Bhagavad Gita or "The Divine Song", Yoga Sutras of Patañjali), philosophical (Marcus Aurelius, Epictetus, Keirkegaard, Krishnamurti, Lao Tzu, Watts), as well as in other various literary forms such as romance (Austen), modernism (Nabok), realism (Tolstoy), poetry or theater (Shakespeare). Acceptance requires a person to tolerate experiences as given; otherwise, simply someone will only pursue pleasure, run away from pain and be prone to judge experiences. The Stoics (Marcus Aurelius, Epictetus, Seneca) appreciated the ability to tolerate or willingly resist experiences, because it increases the degree of self-control, of detachment without emotion and develops indifference to pleasure and pain. Since acceptance involves contact with reality as it is at a certain moment, it is necessary to be able to remain present and aware even when the available stimuli are less desirable. Consequently, tolerance can be considered a skill through which we can remain present and experience anything that happens completely.